Molecular Analysis of Glutamate Decarboxylases in Enterococcus avium - Gu, Xinyi; Zhao, Jiancun; Zhang, Rongling; Yu, Ruohan; Guo, Tingting; Kong, Jian (Frontiers in Microbiology, 2021)
Enterococcus avium (E. avium) is a common bacterium inhabiting the intestines of humans and other animals. Most strains of this species can produce gamma-aminobutyric acid (GABA) via the glutamate decarboxylase (GAD) system, but the presence and genetic organization of their GAD systems are poorly characterized. In this study, our bioinformatics analyses showed that the GAD system in E. avium strains was generally encoded by three gadB genes (gadB1, gadB2 and gadB3), together with an antiporter gene (gadC) and regulator gene (gadR), and these genes are organized in a cluster. This finding contrasts with that for other lactic acid bacteria. E. avium SDMCC050406, a GABA producer isolated from human feces, was employed to investigate the contribution of the three gadB genes to GABA biosynthesis. The results showed that the improvement of relative expression level of gadB3 was higher than those of gadB1 and gadB2 in the exponential growth and stationary phases, and this was accompanied by the synchronous transcription of gadC. After heterologous-expression of the three gadB genes in E. coli BL21 (DE3), the Kmm value of the purified GAD3 was 4.26 ± 0.48 mM, a value lower than those of the purified GAD1 and GAD2. Moreover, gadB3 gene inactivation caused decreased GABA production, accompanied by a decline reduction in resistance to acid stress. These results indicated that gadB3 plays a crucial role in GABA biosynthesis and this property endowed the strain with acid tolerance. Our findings provided insights into how E. avium strains survive the acidic environments of fermented foods and throughout transit through the stomach and gut while maintaining cell viability.